Performance and microbial community analysis of dry anaerobic co-digestion of rice straw and cow manure with added limonite. (July 2019) - Xu, Lifeng; Peng, Shuchuan; Dong, Dingshuo; Wang, Chen; Fan, Wenrui; Cao, Yong; Huang, Fen; Wang, Jin; Yue, Zhengbo
Abstract: Dry anaerobic digestion is a promising technology for recovering energy from agricultural waste. The aim of this study was to investigate the effect of limonite on the dry anaerobic co-digestion of rice straw and cow manure. The maximum methane generation rates were found to increase by 30.5 ± 2.2%, 20.5 ± 1.9%, and 18.7 ± 1.8% in the reactors with limonite concentrations of 1%, 5% and 10%, respectively. The methane yield was also improved by the addition of limonite. This effect was attributed to the ability of limonite to enhance the degradation efficiency of soluble organic metabolites. The efficiency of crude protein degradation was 38.1 ± 6.6%–45.9 ± 6.0% with limonite addition, which was significantly higher than the value of 26.2 ± 3.7% in the control. The abundance of microorganisms associated with protein or amino acid decomposition increased with limonite addition. Hydrogen-consuming methanogenesis by Methanofollis was dominant in the reactors. Highlights: Limonite facilitated the dry anaerobic digestion process of organic wastes. Limonite promoted the methane generation rate in dry anaerobic digester. Limonite improved the abundance of hydrogen-consuming methanogenesis. The degradation efficiency of crude protein in the feedstocks was improved.